The Family Resolutions Specialty Court (FRSC): An Evidence‐Informed Court‐Based Innovation. (30th September 2021) - Pruett, Marsha Kline; Alschech, Jonathan; Feldscher, Talia
Abstract : This article looks at how four distinct programs contributed to the family law evidence‐base supporting the desirability, effectiveness and cost‐effectiveness of family dispute resolution programs. The central program discussed is the Family Resolutions Specialty Court (FRSC), an alternative court‐based means of settling child‐related legal disputes. FRSC is based on research evidence, but it also incorporates clinical experience and wisdom along with empirical evidence. Evidence from similar models informed the development of the program, which was then shaped by a community process to reflect local laws, procedures and values. This maximized the potential for its acceptance in the community and its sustainability. Initial results demonstrate that parents and practitioners are highly satisfied with the program, and that parents reported better coparenting and parent–child relationships. To be effective, the parents had to be held accountable to each other and the court process. A process evaluation (research about the program) led to programmatic and procedural changes to serve the needs of parents in high conflict or with other special needs. FRSC provides a prime example of how to utilize science‐based evidence to adapt evidence‐informed programs to a local community in which it can thrive. Key Points for the Family Law Community: Best practices dictate that implementing or scaling up intervention models begins with a community‐wide input process that facilitates community acceptance and sustainability through ongoing community support. Defining characteristics of the Family Resolutions Specialty Court (FRSC) include parents' self‐determination; focus on needs and interests, not rights; positive communication, and informality in the process while holding to legal rules and procedures. FRSC offers clinical (case management), educational (parenting/coparenting, emphasis on communication) and legal (mediation, drafting agreements, child's attorney) program components. Programs based on and backed by evidence are likely to have the greatest impact; therefore, family law practitioners of all disciplines should have knowledge of and support evidence‐informed and evidence‐based programs.